STABILITY REGION OF TROJAN OBJECTS IN EXTRASOLAR PLANETARY SYSTEM - Surya Guritno, Cometta
Computer simulations can help out to verify the stability of extrasolar planetary systems. The stability of an object residing in the Triangulation (Trojan) regions of a planet can be examined and determined by orbit simu- lations of hypothetical objects. We investigated four extrasolar planetary systems (HD 183263, HD 73526,HD 163607, and HD 4732) which are, respectively, currently known to harbour two planets, whose one of them (Jupiter-massed) is located inside the habitable zone. A number of hypothetical objects, if their orbits are stable, will indicate the possibility that an Earth-massed planet can be existent inside the habitable zone. The simulations are conducted for 10 million years to verify the stability. The simulation result shows instability for hypothetical Trojan objects in the HD 183263 system. Trojan objects in HD 73526 and HD 163607 systems have chances of stability, if the mass of the inner planet is included into the mass of the star. With this mass inclusion, the HD 73526 and HD 163607 systems have stability regions in the longitudes of periapsis (degree) of about 60-84 (and 300-324), and about 38-91 (and 268-321) with respect to the outer planet. Without the mass inclusion of the inner planet (HD 4732 b), the simulations of HD 4732 system show stability regions after 10 million years in the longitudes of periapsis of 40-90 and 270-320 degree (symmetric) with respect to the outer planet (HD 4732 c), which resides inside the habitable zone. This work also shows that an order of Earth-massed planet, in the habitable zone, can be stable in the Trojan regions of HD 4732 c.